The Role of Farmer Groups and Willingness to Pay in Farmers' Interest in Paddy Farming Insurance (AUTP) - Dalmiyatun, Tutik; Sumekar, Wulan; Prayoga, Kadhung (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 18 No 2 (2024): Vol 18 No 2 (2024)DO - 10.24843/SOCA.2024.v18.i02.p07, 2024)
Agricultural insurance is a preventive measure to protect farmers from crop failure losses. Despite the availability of insurance, the interest of farmers in Pekalongan remains low. This study aims to analyze the role of farmer groups in the interest in the paddy farming insurance product (AUTP) and to analyze farmers' willingness to pay. The research was conducted using a quantitative approach, with the population being paddy farmers in Tirto District, Pekalongan Regency. The location was determined purposively, targeting areas implementing the AUTP program. Respondents included both land-owning and tenant paddy farmers. Secondary data included supporting data related to the AUTP program. Data were analyzed descriptively and with multiple regression to assess the role of groups and willingness to pay in influencing respondents' interest. The study found that 82.98% of respondents were of productive age, with predominantly low education levels, mostly elementary school, and farmland areas of less than 1 hectare. About 51% of respondents earned an agricultural income of approximately IDR2,000,000 per month. The study results indicate that willingness to pay and the role of groups, particularly in learning classes, influence interest in the AUTP program. Farmer groups play an educational role where farmers receive information on procedures and claims of AUTP through group information and coordination. The role of farmer groups significantly aids farmers in the AUTP program implementation process, thus requiring increased awareness through intensified assistance